Early Immunogenicity and Safety of the Third Dose of BNT162b2 Messenger RNA Coronavirus Disease 2019 Vaccine Among Adults Older Than 60 Years: Real-World Experience. (29th November 2021) - Gilboa, Mayan; Mandelboim, Michal; Indenbaum, Victoria; Lustig, Yaniv; Cohen, Carmit; Rahav, Galia; Asraf, Keren; Amit, Sharon; Jaber, Hanaa; Nemet, Ital; Kliker, Limor; Bar-Haim, Erez; et al.
Abstract: Background: Despite high vaccine coverage, an increase in breakthrough coronavirus disease 2019 (COVID-19) infections, prompted administration of a third BNT162b2 dose to people aged >60 years in Israel since July 2021. Here, we report real-world immunogenicity following third dose. Methods: Overall, 208 healthcare workers aged >60 years were included. Paired pre– and post–second and/or third dose immunoglobulin G (IgG) and neutralizing antibody titers were compared. A subpopulation of low responders to the second dose was also tested for T-cell activation. For 25 paired serum samples, we tested neutralization of wild-type vs neutralization of Delta and Lambda variants, pre– and post–third dose. Active surveillance of vaccine adverse events was conducted through surveys. Results: A pronounced immune response was observed following the third dose, including a 33-fold and 51-fold increase in IgG and neutralizing antibody, respectively. The neutralizing antibody levels post–third dose were 9.34 times higher than post–second dose (geometric mean titer, 2598 [95% confidence interval CI, 2085–3237] vs 207 [95% CI, 126–339]). Nine previously low responders had a significant antibody increase post–third dose, and 7 of 9 showed increase in T-cell activation. Additionally, sera obtained post–third dose highly and comparably neutralized the wild-type and Delta and Lambda variants. Of 1056 responders to the adverse-event survey, none had serious events. Conclusions: We demonstrate a rapid and broad immune response to the third BNT162b2 dose in individuals >60 years of age. Abstract : A rapid and broad immune response to the third BNT162b2 dose in 208 individuals aged >60 years is reported (33-fold and 51-fold increase in IgG and neutralizing antibody, respectively). Levels post–third dose were significantly higher than post–second dose.